Azospirillum brasilense can impressively improve growth and development of urochloa brizantha under irrigation - Moreira, Bruno Rafael de Almeida [UNESP]; Viana, Ronaldo da Silva [UNESP]; Favato, Vinícius Lopes [UNESP]; de Figueiredo, Paulo Alexandre Monteiro [UNESP]; Lisboa, Lucas Aparecido Manzani [UNESP]; Miasaki, Celso Tadao [UNESP]; Magalhães, Anderson Chagas [UNESP]; Ramos, Sérgio Bispo [UNESP]; Viana, Charlene Raquel de Almeida [UNESP]; Trindade, Vanessa Dias Rezende [UNESP]; May, André (MDPI, 2020)
Development of strategies to ensure grazing systems are sustainably produced in harsh environments, while not fertilizing them conventionally, is challenging. Figuring out the extent to which dose of inoculation and period of watering can positively influence the establishment of an effective symbiosis between U. brizantha cv. Marandu and Azospirillum brasilense is the point of this research. The treatment consisted of mixing 1 kg seeds with the inoculant of the strains Ab-V5 and Ab-V6 at 5, 10, 20, and 40 mL kg−1, 2 x 108 CFU mL−1. The plants grew in pots watered 2, 4, 8, and 16 days after sowing over thirty-days, twice. The bioagent at 5–10 mL kg−1 enabled the plants watered up to 4 days after sowing to peak the production of dry mass of shoots (28.50 g) and roots (12.55 g). The efficiency of the symbiosis goes down quickly with increasing dose and delay of watering. Hence, if the dose of inoculant is higher than 10 mL kg−1, it cannot successfully act in plants watered at least 8 days after sowing anymore. In conclusion, A. brasilense can assist in U. brizantha cv. Marandu growth and healthy development unless a lack of water in the substrate and an overdose collectively deter its potential.
Keywords: Foraging-crop; Palisade-grass; Plant growth-promoting bacterium; Rhizobacterium